Novel Concepts for Intrauterine Device Placement at Caesarean Delivery: Description of Technique and Video Recording - G. Justus Hofmeyr; Kyungu M. Kime (Hindawi Limited, 2023)
The International Federation of Gynaecology and Obstetrics recommend digital insertion of the copper intrauterine device (IUD) during caesarean delivery and note the risk of thread inclusion in the uterotomy closure and nonvisibility of threads at follow-up. We describe a novel method of inserting the IUD with the insertion straw and directing the lower end of the straw through the cervix for retrieval after the operation, to protect and ensure alignment of the threads. We also describe a simple method of lengthening one thread with part of the other thread, to avoid risks associated with braided suture extensions.